Photo-induced copper-mediated (meth)acrylate polymerization towards graphene oxide and reduced graphene oxide modification - Railian, Svitlana; Haven, Joris J.; Maes, Lowie; De Sloovere, Dries; Trouillet, Vanessa; Welle, Alexander; Adriaensens, Peter; Van Bael, Marlies K.; Hardy, An; Deferme, Wim; Junkers, Tanja (European polymer journal, 2020)
[Display omitted] •Graphene oxide has been grafted via photo-controlled copper-mediated polymerization.•Grafting-to and grafting-from methods are compared to elucidate best procedures.•High grafting densitities have been reached.•The grafting reaction is scalable via continuous flow techniques.•Detailed characterization of the graphene oxide sheets is provided (NMR, XPS, TGA, FT-IR) The preparation of well-dispersed graphene/polymer nanocomposites is challenging due to the poor miscibility of graphene sheets in a polymer matrix. To enhance the interaction between both phases, graphene sheets can be decorated with polymer chains. Herein, different strategies to graft poly(methyl methacrylate) (PMMA) and poly(di(ethylene glycol) ethyl ether acrylate) (PDEGA) chains at various positions on graphene oxide and reduced graphene oxide (GO/rGO) sheets are compared. Chain attachment was achieved by “grafting-to” and “grafting-from” methods. Grafting-to was performed by classical copper (I)-catalyzed alkyne azide cycloaddition. Using a grafting-from approach, PMMA and PDEGA brushes were grown from GO and rGO sheets via surface-initiated photo-induced copper-mediated polymerization (SI-photoCMP). SI-photoCMP is a robust and efficient method that allows polymerizations to be carried out under mild conditions and with reduced catalyst concentration. Moreover, the successful implementation of SI-photoCMP in a continuous-flow set-up enables easy upscaling of the system and is, therefore, a more efficient and environmentally friendly process for GO/rGO surface modification. By using the grafting-to approach, the grafting density of PMMA (Mn = 2,600 g/mol) was one chain per 990 carbons of graphene. In contrast, longer PMMA chains (Mn = 40,300 g/mol) and higher grafting density were obtained via the grafting-from method (one PMMA chain per 140 carbons of graphene).